Extrinsic and Intrinsic Motivation to Improve the Quality of Public Services: A Case Study at the Rumah Sakit Umum Daerah (RSUD) Cengkareng - Mira Permata Sari; Baby Poernomo; Mara Elaiza Augustine Flores; Nataya Premchaiporn (Ilomata International Journal of Social Science, 2022)
This research is intended to answer the questions how the employees of RSUD Cengkareng can improve the quality of their services with extrinsic and intrinsic motivation and what are the obstacles encountered in improving the service quality of RSUD Cengkareng. Data collection methods in this qualitative research are interviews and documentation. The interviews conducted were semi-structured interviews. Researchers conducted interviews with 20 non-medical employees with the criteria of having worked for more than 5 years to obtain data on whether employees have intrinsic motivation to work and provide excellent service to patients and whether the leadership at Cengkareng Hospital provides extrinsic motivation to employees so that they can continue to work. improve services to patients. To get more objective results, the researchers also interviewed 20 Cengkareng Hospital patients, in order to obtain data related to how the services provided by the employees at Cengkareng Hospital. The results of this study indicate that extrinsic motivation given by superiors is highly expected by employees so that employees' intrinsic motivation can increase to provide better services to patient.